Care needs of children with chronic illnesses from the perspectives of children, parents, and nurses: a Q methodology approach - Güneş San, Emine; Celik, Rukiye; Altay, Naime; Şan, Emine Güneş (Bmc, 2025)
Background: Understanding the care needs of children diagnosed with chronic diseases and their parents is essential for quality nursing care. Aim: This study aimed to determine the priorities of the needs of the children diagnosed with chronic diseases, their parents, and the nurses caring for them. Methods: This exploratory study was conducted in the Gazi University. Data were collected using the Q methodology approach. 41 people (18 children, 18 parents, and 5 nurses) participated in this study. The study involved 23 cards sorted separately by children (n = 18), their parents (n = 18), and nurses (n = 5). The cards were ranked from (+ 3) to (-3) from most important to least important. The factor array of each statement, Z score value, distinguished reports (p < .05, p < .01). Results: Q factor analysis revealed four factors for children, five for parents, and two for nurses. The essential needs for children are that the nurse should Be smiling and approachable and Provide information about the illness. Similarly, the necessary need for parents is that nurses Provide information about the illness. Conclusion: It is essential to know the care needs of children and parents to provide good quality care. Clinical trial number: Not applicable.
Keywords: Child; Chronic Diseases; Parents; Nurses; Needs Assessment